Too much or too little? Exploring effort perception in schizophrenia within the framework of motivational intensity theory. Issue 4 (3rd July 2020) - Décombe, Amandine; Brunel, Lionel; Capdevielle, Delphine; Raffard, Stéphane
ABSTRACT: Introduction: To explain motivational difficulties in schizophrenia (SZ), attention has focused on the reward system and effort-based decision-making deficits. However, according to motivational intensity theory (MIT), effort is not directly determined by reward but by task difficulty. Moreover, no studies have examined the effort perception in the SZ. Therefore, this cross-sectional study compared effort perception in SZ group with healthy controls. Method: Task difficulty was manipulated by increasing the distance covered (from 8 to 48 metres). Walking speed, perceptions of difficulty and effort were assessed for all difficulty levels. Clinical and bodyweight variables were recorded. Results: As postulated by MIT, perceived effort and difficulty increased with task difficulty in both groups. Perceived effort and difficulty were higher in the SZ group. Perceptions of effort were positively correlated with BMI in SZ, but not with clinical variables. Importantly, although SZ patients perceived the task as more effortful, walking speed was similar between groups. Conclusions: Taken together, these results suggested that individuals with SZ perceived more strongly the effort and the difficulty of the task but could mobilise more effort to complete it. This observation may explain in part the decrease in engaging in physical demanding activities in daily life in SZ.